Impact of sleeve gastrectomy on the periodontal status of patients with and without type 2 diabetes: a 1-year prospective real-world study - Bi, Xiaocheng; Zhao, Peikai; Liu, Teng; Zhu, Tao; Li, Yuxuan; Xiong, Sisi; Liu, Shaozhuang; Hu, Xiaole; Huang, Xin (Frontiers in Endocrinology, 2024)
Background: Periodontitis is a chronic inflammatory disease potentially associated with obesity and type 2 diabetes (T2D). Sleeve gastrectomy (SG) has shown substantial effect on weight loss and treatment of T2D. However, there is no direct evidence comparing the impact of SG on the periodontal status of patients with and without T2D.To determine the impact of SG on the periodontal status of patients with and without T2D in a real-world setting. Methods: In a prospective and two-armed cohort design, participants who were scheduled for SG at an affiliated hospital between April 2022 and December 2022 were approached for eligibility. After a clinical evaluation and oral examination, those with periodontitis were included and further divided into the DM group (diabetic) and the Control group (non-diabetic) with a 1-year follow-up after surgery. The primary outcome was the periodontal status of patients at 12 months after SG. The secondary outcomes included weight loss, diabetes remission, and alterations in inflammatory markers for up to 1 year after SG. Results: Fifty-seven and 49 patients were included in the DM and the Control group, respectively.Before surgery, patients in the DM group had further worsened periodontal condition compared with those in the Control group. Accompanied by weight loss and glucose reduction, patients in both groups demonstrated significant decreases in plaque index (PLI) and bleeding index (BI) with no alterations in probing depth or clinical attachment loss for up to 1 year after SG. Even patients in the DM group achieved less TWL% (32.79 ± 6.20% vs. 37.95 ± 8.34, P<0.01), their periodontal condition had more substantial improvement with no significant difference in PLI and BI between groups at 1 year after SG. We also observed a significant reduction in the levels of high sensitive C-reactive protein and interleukin-6 in both groups at 1 year after SG. Conclusion: Both patients with and without T2D demonstrated improved periodontal status for up to 1 year after SG. Patients with T2D achieved less weight loss but a more substantial improvement in periodontal condition. The significant reduction in inflammatory biomarkers contributed to the improvement of periodontal status after SG.